1981
DOI: 10.1159/000198667
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Alternate Day Prednisolone as a Maintenance Treatment for Ulcerative Colitis in Remission

Abstract: A double-blind crossover trial compared prednisolone, 40 mg given orally on alternate days, with placebo as a maintenance treatment for ulcerative colitis in remission. In each patient, the study was over two periods of 3 months. Of 24 patients who completed both periods, 11 relapsed while taking placebo but did not while taking prednisolone, and 1 relapsed on prednisolone but did not on placebo (p < 0.01). 1 patient had to stop prednisolone because of hyperglycaemia; other side effects noted were mild. Predni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Neither cortisone 50 mg daily [467] nor prednisone up to 15 mg daily [468] was effective at preventing relapse. While high-dose (40 mg) alternate-day prednisone in addition to sulfasalazine did reduce relapse rates in a small, 24-patient trial, side effects of oral corticosteroids rarely justify their long-term use [110,111,391,463,469].…”
Section: Oral Corticosteroidsmentioning
confidence: 96%
“…Neither cortisone 50 mg daily [467] nor prednisone up to 15 mg daily [468] was effective at preventing relapse. While high-dose (40 mg) alternate-day prednisone in addition to sulfasalazine did reduce relapse rates in a small, 24-patient trial, side effects of oral corticosteroids rarely justify their long-term use [110,111,391,463,469].…”
Section: Oral Corticosteroidsmentioning
confidence: 96%
“…1,2,20 Recent studies have shown that prednisolone is suitable as a maintenance treatment for UC in remission, although about 40 mg in an alternate-day dose is required. 20 c-GCS, when administered for either therapy of active disease or maintenance treatment of UC or CD, may lead to severe steroid side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,20 Recent studies have shown that prednisolone is suitable as a maintenance treatment for UC in remission, although about 40 mg in an alternate-day dose is required. 20 c-GCS, when administered for either therapy of active disease or maintenance treatment of UC or CD, may lead to severe steroid side-effects. 5,21 In other studies, patients with chronic active or frequently relapsing disease have been treated with azathioprine or 6-mercaptopurine, leading to complete remission in many cases and allowing termination of therapy with corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Placebo-controlled studies have not been performed; however, several papers described the effect of intravenous corticosteroids in this group of patients, showing a general response rate of approximately 50% [15,16,17,18]. Contrary to their effect on the induction of remission, corticosteroids have not been shown to be beneficial for the maintenance of remission of UC [19, 20], and, together with the presence of a high frequency of side effects, currently available data do not support the use of corticosteroids for maintenance therapy.…”
Section: Currently Available Therapies For Ucmentioning
confidence: 99%